IAQ and CFD study on the ventilation system in a chassis dynamometer room - Mohamed Ejledi, Alaeddin (2011)
The chassis dynamometer room is one of many extensions in the automotive laboratory, UTHM, which is one of a few dynamometer rooms available in Malaysia. Consequently, it becomes highlighted facility to do tests and researches with respect to vehicle components such as the braking, cooling, and electrical systems. The major application however is to evaluate engine performance. Ventilation system is an essential system to reduce the air pollution, thus maintain acceptable indoor air quality (IAQ) in any chassis dynamometer room. Currently, the room depends on two types of ventilation: natural ventilation through two windows and a door, enhanced with mechanical ventilation which is an exhaust fan placed on the top of the room. Unfortunately, the existing ventilation system is not sufficient to support activities conducted in the room as was proven in the IAQ study. Therefore in the current study, results of a computational fluid dynamics (CFD) for air flow and thermal distribution in the tested room are presented. CFD results expose the weaknesses of the existing system. Thus, a much better air flow structure and thermal distribution as required shall be provided by the installation of a new improved ventilation design as proposed in this study.